Noms, étiquette(s) et identités dans Persuasion, de Jane Austen - Marie-Laure Massei (Cahiers Victoriens et Edouardiens)
Jane Austen’s last novel, Persuasion, dramatises the tensions inherent in the decline of the ancient landed order and of its traditional sources of authority, as the emergence of a new social hierarchy, in the wake of the Napoleonic wars, was leading to a questioning of signifiers: patronyms and titles are thus subject to constant reassessment in the novel while the honorific term ‘gentleman’ is threatened with devaluation. Labelled a ‘nobody’ at the beginning even though she embodies sense, constancy and fortitude, Anne Elliot is reborn as a heroine through her ability to read and decipher meanings, manners and behaviours: her new status and identity are then aptly signified by a telling mutation of the signifier after her marriage, freeing her from the sterile codes of the paternal narrative.